INCREASING GROUND WATER DEPENDENCY AND DECLINING WATER QUALITY IN URBAN WATER SUPPLY - A COMPARATIVE ANALYSIS OF FOUR SOUTH INDIAN CITIES - K V Raju, N Latha S Manasi (INSTITUTE FOR SOCIAL AND ECONOMIC CHANGE, 2007)
This paper examines the extent of groundwater dependency and quality status in Hubli, Dharwad, Belgaum and Kolar cities in the context of National Water Policy. Household survey indicated dependency of 30, 51, 37 and 100 percent while the quality analysis indicated 45, 42, 22 and 97 percent as non-potable in the above cities respectively. Water markets captured a turnover of Rs. 50 crore in Hubli, Dharwad and Belgaum whereas in Bagepalli taluk, Kolar district alone, was Rs.120 million/annum.